2022
DOI: 10.1177/1934578x221111037
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Akkermansia muciniphilia Growth Associated With Spring Water Ingestion Prevents Obesity and Hyperglycemia in a High-fat Diet-Induced Mouse Model

Abstract: Background: Type 2 diabetes may be alleviated by mineral water (MW) ingestion. We investigated whether spring water (SW) (a kind of mixed MW) ingestion influences metabolic parameters via alteration of the gut microbiota in high-fat diet (HFD)-fed mice. Method: We divided 32 C57/BL mice into 4 equal groups: normal diet with tap water (Control), high-fat diet with tap water (HFD), normal diet with SW (SW), and high-fat diet with SW (HFD + SW). During this experiment, we checked the body weight (BW) with fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…When intestinal permeability increases, excessive endotoxin can enter the blood circulation and trigger inflammation cascade reaction and disrupt homeostasis of intestinal barrier function [16] . Recent studies have confirmed that increased intestinal permeability and intestinal-derived LPS translocation are important causes of metabolic inflammation in T2DM [17][18] . Therefore, targeting intestinal barrier is a promising strategy for the treatment of T2DM.…”
Section: Introductionmentioning
confidence: 91%
“…When intestinal permeability increases, excessive endotoxin can enter the blood circulation and trigger inflammation cascade reaction and disrupt homeostasis of intestinal barrier function [16] . Recent studies have confirmed that increased intestinal permeability and intestinal-derived LPS translocation are important causes of metabolic inflammation in T2DM [17][18] . Therefore, targeting intestinal barrier is a promising strategy for the treatment of T2DM.…”
Section: Introductionmentioning
confidence: 91%